3D Printing: 3D‐Printed Structural Pseudocapacitors (Adv. Mater. Technol. 9/2016). Issue 9 (December 2016) - Liu, Xinhua; Jervis, Rhodri; Maher, Robert C.; Villar‐Garcia, Ignacio J.; Naylor‐Marlow, Max; Shearing, Paul R.; Ouyang, Mengzheng; Cohen, Lesley; Brandon, Nigel P.; Wu, Billy
Abstract : Structural energy storage devices have the potential to transform products such as aerial vehicles, cars and consumer electronics. In article number 1600167, Xinhua Liu, Billy Wu, and co‐workers use direct metal laser sintering to create 3D hierarchical scaffolds with high mechanical strength. Functionalisation with MnOx ‐PEDOT:PSS imparts the structure with pseduocapacitive properties and multi‐scale x‐ray tomography highlights how this approach improves device performance and lifetime.